Density functional theory study of Al-doped hematite - Rivera Escobar, R. (2011)
Using first-principles density functional theory calculations within the generalized gradient approximation (GGA) as well as the GGA+U approach, we study Al-doped ?-Fe 2O 3 crystals. Structural, electronic, magnetic and optical properties due to impurity incorporation have been investigated and discussed in detail. Atomic displacements and Bader charges on atoms have been computed, showing that Al dopant converts the chemical bonding in its neighbourhood into a more ionic one. This work enhances our knowledge about how a crystalline lattice reacts in the presence of an Al impurity. It was found that Al incorporation produces some local changes in the band structure of the material without the creation of local energy levels within the band gap. The results provide evidence for changes in the magnetic moments in the vicinity of a defect, which means that ?-Fe 2O 3 doped with aluminum might not act as an antiferromagnetic substance.